Land use mapping by GIS - ANU M. BABU; Ramya P; Smitha K. E; Er. Vishnu B (Guide) (Tavanur 2005 Kelappaji College of Agricultural Engineering and Technology)
Land use mapping by GIS
Land use mapping by GIS